Comparison of the safety and efficacy of low fluence Q‐switched 1064‐nm and conventional Q‐Switched 755‐nm lasers in the treatment of café‐au‐lait macules: A prospective self‐controlled trial. Issue 8 (9th September 2022) - Cen, Qingqing; Zhu, Jiafang; Zhou, Lucia; Yu, Wenxin; Wu, Xianglei; Liu, Ying; Ma, Gang; Luo, Lan; Lin, Xiaoxi
Abstract: Background: Conventional high fluence Q‐switched (HFQS) Alexandrite 755‐nm are widely used in clinical café‐au‐lait macules (CALMs) treatment. There have been recent concerns regarding the efficacy and safety of low fluence Q‐switched (LFQS) Nd: YAG 1064‐nm lasers. Objective: To evaluate the efficacy and safety of the conventional HFQS and LFQS laser in the treatment of CALMs. Methods: Within 3 months, 20 patients underwent prospective self‐controlled split‐lesion treatments with HFQS once or twice depending on the recovery rate, and with LFQS six times biweekly. Then the more effective laser was selected for continued treatments. Efficacy outcomes were evaluated by a visual analog scale (VAS) biweekly during the comparative trail. Recovery process, side effects and recurrence were recorded during the trial and follow‐up visit. Patient and physician preferences for laser selection were also recorded. Results: The average VAS scores of areas treated with HFQS and LFQS were 2.92 ± 0.86 and 2.93 ± 1.13, respectively ( p > 0.05). The most significant efficacy change of LFQS was after the fourth laser treatment (VAS score: 1.82−2.37, p < 0.001). 11 lesions treated with LFQS and 7 with HFQS achieved an optimal treatment response (3.67 ≤ VAS ≤ 4). Three patients relapsed on one side (one on LFQS, two on HFQS) and five on both sides. Adverse effects included temporary hypopigmentation, hyperpigmentation, uneven pigmentation, and mottled hypopigmentation. Doctors thought 80% of patients were suitable for LFQS. 70% of patients preferred LFQS posttreatment. Conclusions: The efficacy difference between the LFQS 1064‐nm laser and HFQS 755‐nm laser in treating CALMs in a 3‐month comparative trial was statistically insignificant. LFQS is preferred by doctors and patients and is likely to help more patients achieve treatment efficacy than the HFQS within a short time, with fewer temporary adverse reactions, and a more even pigmentation. But it can cause mottled hypopigmentation. The LFQS had obvious lesion clearance after the fourth treatment.